Online Based Community Empowerment in Bukian Village, Bali as an Effort to Prevent Covid19 Transmission - Pande Ayu Naya Kasih Permatananda; Anak Agung Sri Agung Aryastuti; Putu Nita Cahyawati; Desak Putu Citra Udiyani (Global Health Science Group, 2020)
Preventing COVID19 transmission in community is currently important. As one of villages located close to Bali’s tourism centre, Bukian village is expected to be more vigilant in preventing the spread of COVID19. However, the public knowledge about COVID19 was low, the people was careless with pandemic situation, and public socialization was limited, making the effort in preventing the transmission of the disease at that time had not run optimally. This community empowerment activities lasted for 1 month in the form of providing education with online methods and intensive mentoring of one student, one participant, targeting families and members of the COVID19 task force, with a sum of 10 students and 10 participants. All activities went well and enthusiasm of participants was quite good. Pre-test and post-test questionnaires were given to evaluate the increase in the knowledge and attitudes of the participants, then analyzed by wilcoxon test and there was a significant increase in knowledge and attitude of participants (p value <0,05).